2015
DOI: 10.7763/joebm.2015.v3.222
|View full text |Cite
|
Sign up to set email alerts
|

Personality Antecedents of Online Buying Impulsiveness

Abstract: Abstract-The hierarchical relationships of personality traits related to online buying impulsiveness were empirically examined. The results show that three elemental traitsagreeableness, need for arousal, and need for material -are predictive of online buying impulsiveness. Middle level trait of value consciousness is mediating the effect of conscientiousness and negatively associated with the dependent variable. Index Terms-Online buying impulsiveness, trait theory, 3M model I. INTRODUCTIONOver the past deca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 22 publications
1
5
0
3
Order By: Relevance
“…However, in our study, we did not find strong associations for neuroticism, but we were able to find several effects for extraversion, showing that more extraverted individuals have more favourable attitudes towards online shopping and a higher willingness to buy online. Our mediation model is supported by previous research, showing that personality traits are elemental traits and buying impulsiveness is a surface trait [42], and together, they could augment attitudes and the buying intention. The total effects of extraversion could be explained by the high sociability and flexibility of extraverts, who are more receptive to change, to new things and ideas [45], which is highly significant for enhancing the standard electronic commerce by means of augmented reality.…”
Section: Theoretical Implicationssupporting
confidence: 86%
See 2 more Smart Citations
“…However, in our study, we did not find strong associations for neuroticism, but we were able to find several effects for extraversion, showing that more extraverted individuals have more favourable attitudes towards online shopping and a higher willingness to buy online. Our mediation model is supported by previous research, showing that personality traits are elemental traits and buying impulsiveness is a surface trait [42], and together, they could augment attitudes and the buying intention. The total effects of extraversion could be explained by the high sociability and flexibility of extraverts, who are more receptive to change, to new things and ideas [45], which is highly significant for enhancing the standard electronic commerce by means of augmented reality.…”
Section: Theoretical Implicationssupporting
confidence: 86%
“…Personality traits as determinants or antecedents of buying behaviour have lately become an important topic of research. The Big Five model of personality seems to be the most used model, offering a subset of elemental traits efficient in predicting buying behaviours [42]. Ref.…”
Section: Personality Antecedents Of Online Buying Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Dalam beberapa penelitian sebelumnya telah didapati bahwa traits kepribadian yang terkait dengan faktor psikologis, disebut memiliki keterkaitan dengan impulsive buying konsumen (Chen & Lee, 2015;Shahjehan dkk., 2012;Verplanken & Herabadi, 2001). Traits sendiri dapat dijelaskan sebagai sistem kebiasaan dan kumpulan sifat-sifat yang merupakan komponen dasar dari kepribadian (Allport, 1922dalam John dkk., 2008.…”
Section: P E N D a H U L U A Nunclassified
“…Furthermore, research has demonstrated that impulsivity is associated with the decision-making process of consumers, both offline and online (Huang and Kuo, 2012). Consequently, online buying impulsiveness has been scrutinized several times (Chen and Lee, 2015;Huang and Kuo, 2012;LaRose and Eastin, 2002). Although these studies focus on when and how impulsive purchasing occurs, it is to be expected that a relationship between impulsivity and online purchasing behavior exists.…”
Section: Propensity Theories and Impulsivitymentioning
confidence: 99%